A tale of two ivory towers. A comparative analysis of victimization rates and risks between University students in the United States and England - Fisher, Bonnie S. (The British journal of criminology, 2003)
Based on victimization surveys of two random samples of students who live on campus at comparable universities in the United States and England, we examined the extent and nature of on-campus student victimization and students' on-campus risk of experiencing violence, theft, and burglary during an academic year. On-campus victimization rates for students who live on English campuses are overall significantly higher than those who live on US campuses. Guided by lifestyle-routine activity theories, our comparative results from multivariate logit models predicting the likelihood of being an on-campus victim of violence, theft, and burglary reveal that there are more differences than similarities as to which variables significantly predict the probability of being victimized in each country respectively